Panic Buying: Konsumerisme Masyarakat Indonesia di Tengah Pandemi Covid-19 Perspektif Psikoanalisis Jacques Lacan - Astrid Veranita Indah; Awal Muqsith (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
The development of technology in the contemporary era raises various problems of humanitarian crises. The humanitarian crisis was caused by rapid development of capitalist ideology, technology and science. Mass purchases in a short period of time in the midst of the Covid-19 pandemic made subjects consume unnecessary items. The subject has a split in understanding reality. Lacan's psychoanalysis is important in understanding the lifestyle of the consumerist society amid the Covid-19 pandemic. The Lacan trilogy is able to analyze of humans as subjects. The purpose of this study was to determine the background of panic buying behavior in the midst of the Covid-19 pandemic in Indonesia. This research method is a literature study, aimed at analyzing panic buying behavior as a form of consumerism, with the theoretical framework of Jaques Lacan's psychoanalysis. The result of this research is that the currently present subject is a subject in interaction with pure reality which is translated into a symbolic code. A subject who seeks happiness with the desire to be someone else and to calm his panic in an unstable state. The subject considers consumption to be the answer to anxiety symptoms in the midst of the Covid-19 pandemic.